Characterization, Classification and Crop Suitability Evaluation of Some Coastal Soils in Gujarat - Duraisamy Vasu; Humadevi Kuchankar; Neha Gautam; Minal Suryawanshi; Pramod Tiwary; Padikkal Chandran (Journal of the Indian Society of Soil Science, 2024)
Five representative pedons (P1 Chival; P2 Arnad; P3 Paria; P4 Son; and P5 Motiwada) from different landforms of Pardi taluka in the coastal region of Valsad district, Gujarat, were studied for their morphological, physical, and chemical properties, and evaluated for their suitability for the cultivation of rice, sugarcane, and mango. The soils were deep to very deep (100-150 cm), well to excessively drained, neutral to slightly alkaline (pH 6.2 to 8.4), non-saline (EC < 2 dS m-1), low to high in organic carbon (3.0 to 16.3 g kg-1), low in CaCO3 (<5.0%), and medium to high in CEC [39.0 to 55.3 (p+) kg-1]. Soil texture varied from sandy clay loam to clay, with the clay content ranging from 27.4 to 48.4%. Bulk density was lower in Arnad soil (1.23-1.35 Mg m-3) than in the other soils (1.21-1.45 Mg m-3). The saturated hydraulic conductivity (Ks) varied from 1.4 to 23.4 cm hr-1, and it was higher than the critical limit of 1.0 cm hr-1 in all the pedons indicating good water movement in the soils. The exchangeable sodium percentage (ESP) was low (< 5%), and the pedons were generally high in exchangeable magnesium percentage (EMP) (15.2 to 44.5%). The general characteristics of the studied pedons were atypical for coastal soils of western India. The Chival pedon (P1) with > 25 cm thick slickensides was classified as Typic Haplusterts. The Arnad pedon (P2) with cambic horizons was classified as Typic Haplustepts. The pedons P3 (Paria) and P4 (Son) with argillic horizons and high base saturation were classified as Typic Haplustalfs. The Motiwada pedon (P5) with surface cracks and argillic horizons in the deeper layers (65-145 cm depth) was classified as Inceptic Haplustalfs. Most of the pedons were only marginally suitable (S3) for rice, sugarcane, and mango due to limitations such as erosion hazards and poor nutrient availability based on unfavourable soil pH conditions. The results of soil-site suitability evaluation for crops expose the paradox in the Sys method, and therefore, caution needs to be exercised while using the method.